Religious freedom, the Malaysian Constitution and Islam: a critical analysis - Wan Husin, Wan Nurhasniah; Ibrahim, Haslina (Elsevier, 2016)
This article seeks to analyze three types of religious freedom as stipulated by the Malaysian Constitution; freedom to profess, freedom to practice and freedom to disseminate one’s religion. The article will also analyze whether the provisions on freedom adhere to the objectives of Islamic laws (maqasid al-shari’ah) given that Islam is regarded by the Constitution as the religion of the Federation and practically the religion of the majority. In addition, the Charter of Medina will be taken as a concrete model of which policies on religious freedom can be emulated. The author has combined the textual, contextual, historical and comparative methods in the gathering and the analysis of data. It is hope that the article can provide a critical analysis on religious freedom in Malaysia from an Islamic perspective given that the Constitution is explicit about Islam as the religion of the Federation.